Demon thief - Shan, Darren (New York : Little, Brown, 2006)
With the opening of a window into a demon world, a boy discovers his powers as a Disciple and his mission to hunt the viciously powerful Demonata to the death.
Keywords: Demonology -- Fiction; Horror stories